2016
DOI: 10.1038/srep32334
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Patterns are Associated with Helicobacter Pylori Infection in Chinese Adults: A Cross-Sectional Study

Abstract: Previous studies indicated that food consumption was associated with Helicobacter pylori infection, but no study has yet investigated the association between Helicobacter pylori infection and dietary patterns. The aim of this study was to evaluate the associations between Helicobacter pylori infection and dietary patterns in Tianjin, China. The final cross-sectional study population comprised 10407 participants. Dietary consumption of participants was assessed via food frequency questionnaire. Factor analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 43 publications
1
33
1
Order By: Relevance
“…A convenience sampling method was used to select participants, thereby limiting the ability to generalize results to the target population. Potential misclassification bias of the main outcome although minimal is possible, Serological testing, could be improved further by using stains having higher sensitivity and specificity than H&E stain such as Giemsa stain, Warthin-Starry silver stain, Genta stain, and immunohistochemical (IHC) (69–93% and 87–90% respectively, versus 90–100%) [ 52 , 53 ]. Moreover, the FFQ administered presents some limitations.…”
Section: Discussionmentioning
confidence: 99%
“…A convenience sampling method was used to select participants, thereby limiting the ability to generalize results to the target population. Potential misclassification bias of the main outcome although minimal is possible, Serological testing, could be improved further by using stains having higher sensitivity and specificity than H&E stain such as Giemsa stain, Warthin-Starry silver stain, Genta stain, and immunohistochemical (IHC) (69–93% and 87–90% respectively, versus 90–100%) [ 52 , 53 ]. Moreover, the FFQ administered presents some limitations.…”
Section: Discussionmentioning
confidence: 99%
“…pylori urease-IgG antibodies were serologically detected using a specific ELISA kit, the Hp Urease Immunogold Testing Kit (Beijing Kangmeitianhong Biotechnology Co., Ltd., Beijing, China). The ELISA kit had a sensitivity of 98.91% and specificity of 98.29% for detecting H. pylori in the populations tested (11).…”
Section: H Pylori Detectionmentioning
confidence: 97%
“…Other authors have consistently observed 2 to 3‐fold levels of protein carbonyls in plasma from H. pylori ‐infected patients compared to healthy counterparts, with these values being reliable indicators of the severity, the prognosis, and the efficacy of the treatment (Ma et al., ; Rajendiran, Zachariah, & Hamide, ). The oxidation of red meat in the stomach infected by H. pylori and the subsequent input of dietary protein carbonylation to the carbonylation of the gastric mucosa may contribute to explaining the profuse number of epidemiological studies linking red meat consumption and H. pylori gastritis (Epplein et al., ; Xia et al., ). The formation of protein carbonyls is irreversible and oxidized proteins are accumulated in injured tissues sustaining the chronicity of the pathological conditions that may eventually lead to the oxidative DNA damage and the neoplasic transformation (Figure ).…”
Section: Pathogenesis Of Dietary Protein Oxidation: Recent Advancesmentioning
confidence: 99%